1984
DOI: 10.1016/s0001-2998(84)80050-1
|View full text |Cite
|
Sign up to set email alerts
|

Lacrimal dacryoscintigraphy

Abstract: Lacrimal dacryoscintigraphy facilitates definite diagnosis of obstructions and stenosis of the lacrimal drainage system with little stress to the patient. Together with x-ray dacryocystography it is an important diagnostic tool especially for pre- and postoperative evaluation of the drainage apparatus. Dacryoscintigraphy is the best method for measuring the dynamics of tear drainage especially in the canaliculi. Although it is not a substitute for other methods in general use, it complements them and expands t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
2

Year Published

1991
1991
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(14 citation statements)
references
References 9 publications
0
12
0
2
Order By: Relevance
“…We realize that the underlying assumption of linear clearance, for the LCR parameter, is generally not met, as disappearance curves seldom are straight. In addition, the T1 parameter may be incorrect when the interval between the start of administration and the start of the dynamic study is long, as many studies have indicated that initial tracer disappearance is very fast [1,3,6,9,10,16,17] Therefore, tracer administration in both eyes should be carried out rapidly by an experienced technician, and should always be complete within 15-20 s, which minimizes the error in the subsequent minute. Another issue in the interpretation of dacryoscintigraphy is the degree of resorption of the tracer by the conjunctival mucosa.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We realize that the underlying assumption of linear clearance, for the LCR parameter, is generally not met, as disappearance curves seldom are straight. In addition, the T1 parameter may be incorrect when the interval between the start of administration and the start of the dynamic study is long, as many studies have indicated that initial tracer disappearance is very fast [1,3,6,9,10,16,17] Therefore, tracer administration in both eyes should be carried out rapidly by an experienced technician, and should always be complete within 15-20 s, which minimizes the error in the subsequent minute. Another issue in the interpretation of dacryoscintigraphy is the degree of resorption of the tracer by the conjunctival mucosa.…”
Section: Discussionmentioning
confidence: 99%
“…Since 1972 lacrimal dacryoscintigraphy has been used and modified by many authors [3,10,12,15]. It can be used under almost physiological conditions and provides quantitative criteria [6,9]. From the scintigraphy study both simple and complex parameters that describe the drainage can be derived [8,9,16].…”
Section: Introductionmentioning
confidence: 99%
“…LS is also termed microscintigraphy, 2 nuclear dacryocystogram, 3 nuclear lacrimal scan, 4 lacrimal scintillography, 5 and dacryoscintigraphy. 6 Considerable variation exists in technique, normative data, analysis, and interpretation. This article reviews the evidence-base, to better understand the indications and interpretation.…”
mentioning
confidence: 99%
“…Galloway et al [23] observed that radiation exposure to the eye lens is approximately 2.7 mGy in conventional radiographic dacryocystography. The radiation exposure during dacryoscintigraphy is normally between 0.014 and 0.021 rads [25].…”
Section: Discussionmentioning
confidence: 99%